Improving water and climate data and decision support tools for climate-smart water management in Ethiopia - Taye, Meron Teferi; Seid, Abdulkarim; Tilaye, R.; Tekleab, S.; Mohammed, M.; Berhanu, B. (International Water Management Institute, 2024)
Water is the medium through which most impacts of climate change on people’s livelihoods and ecosystems are transmitted. Climate change can lead to increasing scarcity of water, intensify variability in rainfall and, thereby, river discharge; and exacerbate the severity of flood, drought and heatwave extremes. Reducing climate-induced water scarcity and enhancing climate resilience to water-related hazards requires well-thought-out actions that include water infrastructure development, putting in place adaptive institutional frameworks, and increasingly developing and employing innovations and future-oriented climate and water data and decision support systems. This report is one of the outputs of the study conducted by the International Water Management Institute (IWMI) as part of the project Prioritization of Climate-smart Water Management Practices. The aim of the study has been to develop recommendations for addressing two of the critical gaps identified for improving climate resilience of water resources management in Ethiopia, namely, (1) inadequate data and information on key hydrological variables that have led to a lack of recent knowledge on water availability, actual water use, water source types and potentials; and (2) a lack of decision support tools that would provide strategic and operational level information and capacity for risk-based planning and management of water resources. The report is based on an analysis of collected data, information gleaned through stakeholder consultations and a review of existing literature on climate and water data, and decision support tools in use in the Awash River Basin and at national level in Ethiopia. This synthesis report focuses on the technical aspects of climate and water data and decision support tools, while the institutional aspects are presented in Sanchez Ramirez et al. 2024. This study conceptualizes climate-smart water management as having three reinforcing objectives: maximize the goods and services that can be produced from the limited water resources; minimize the impact of climate extremes — floods and droughts at multiple scales; curtail the impact of rainfall variability across scales, including small-scale agricultural producers, and enhance water resources planning and management at the basin scale. Key challenges that have been identified include inadequate spatial coverage of hydrometeorological networks; short and, very often, intermittent river discharge data; almost nonexistent water use monitoring; fragmentation of data and inadequate capacity of skilled personnel. There are a number of ongoing efforts by the Ministry of Water and Energy with the aim of addressing these challenges. Weather forecasts are made regularly by the Ethiopian Meteorology Institute (EMI) with attempts to translate these forecasts into their potential impacts on agriculture, water and health. These forecasts and their translation into sector-specific implications need to be improved to make them actionable at lower spatial scales. There is also a need to improve the interoperability of databases and systems to minimize data fragmentation and ensure timely sharing of data. This report presents a conceptual architecture of improved water and climate data and decision support tools, together with specific recommendations for improving hydrometeorological data collection networks, monitoring of agricultural water use, communication of information across scales and decision support tools. The recommendations are intended to provide input for ongoing discussions on improving climate and water data and decision support tools for climateresilient water resources management in Ethiopia.